Creation and de-creation in Simone Weil’s philosophy - Estelrich Barceló, Tomeu (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The present article covers the two philosophic paradigms that are in the base of the Weilian doctrine of the Creation and the De-creation (Décréation). These two paradigms are Greek and Christian-occidental. It is essential referring to the first one because Weil totally assumed its cosmology. Her concept of an enclosed world, in which everything is already given, governed by Necessity, was adopted by Weil since a very early age and she kept it until her death. On the other hand, the Weilian vocabulary takes its sustenance from the Christian-occidental paradigm, which also provides the concept of «Creation» (in the sense of «creatio ex nihilo») and the one that determines, per oppositum, the final meaning that Weil gives to it.
Keywords: creation; de-creation; god; greek cosmology; metanoia; mystic